Ecdysteroids from the Aerial Parts of Paris verticillata. Issue 9 (9th August 2021) - Jiang, Peng; Liu, Yan; Sun, Yan‐Ping; Pan, Juan; Guan, Wei; Xu, Zhen‐Peng; Li, Xiao‐Mao; Wang, Si‐Yi; Mei, Yu; Kuang, Hai‐Xue; Yang, Bing‐You
Abstract: Two new ecdysteroids 14‐epi‐polypodine B (1 ) and 22‐oxo‐hydroxyecdysterone (2 ), along with nine known compounds, polypodine B (3 ), viticosterone E (4 ), 20‐hdroxyecdysone‐2‐acetate (5 ), 22‐oxo‐20‐hydroxyecdysone (6 ), 5‐hydroxyecdysone (7 ), pinnatasterone (8 ), 3‐epi‐20‐hydroxyecdysone (9 ), ecdysterone (10 ) and stachysterone B (11 ), were isolated from the aerial parts of Paris verticillata . The structures of all compounds were elucidated by extensive spectroscopic analysis, quantum chemical calculations and ANN‐PRA/DP4 + probability analysis. Among them, the absolute configuration of compound 1 and 2 was unambiguous determined by ECD. Also, the isolated compounds were assessed for their cytotoxic activities. Compounds 2, 3 and 7 exhibited significant cytotoxic activities against PC12, LN299 and SMCC7721 cells. Abstract :